Don’t sweat the small stuff: a conversation about nanosafety - Fadeel, Bengt; Sayre, Phil (Frontiers in Toxicology, 2023)
Bengt Fadeel and Phil Sayre discuss lessons learned with respect to the safety assessment of nanomaterials, and provide a perspective on current and future challenges.